Determination of employee performance: Analysis of training, work motivation, transformational leadership and organizational culture - Rachman, Subehana; B, Joe Alend Seniza.; Susanto, Primadi Candra; Mustika, Ika (Goodwood Publishing, 2025)
Purpose: This study examines key determinants of employee performance in Indonesia’s maritime sector, focusing on ship crews. It analyzes training, work motivation, transformational leadership, and organizational culture to understand their roles in enhancing crew effectiveness, discipline, and overall productivity. Research Methodology: This study used a descriptive qualitative method with the SALSA framework to review 30 peer-reviewed articles published in the past eight years. Theoretical triangulation involved applying Human Capital Theory, Maslow’s Hierarchy of Needs, Bass’s Transformational Leadership, and Hofstede’s Organizational Culture Framework. Results: The findings reveal that training improves job competence, work quality, and accountability; motivation enhances commitment and timeliness; transformational leadership fosters trust, innovation, and responsibility; and organizational culture strengthens discipline, teamwork, and loyalty. Each variable positively influences employee performance in the maritime context. Conclusions: Investments in human resource factors particularly training, motivation, leadership, and organizational culture are crucial for enhancing the performance of maritime personnel. These factors serve as strategic levers to improve safety, operational efficiency, and service quality in the shipping industry. Limitations: The study is limited to secondary data from literature published in English and Bahasa Indonesia, lacks empirical field validation, and does not explore the interaction effects among the variables. Contribution: This study contributes conceptually by offering a synthesized framework linking human resource variables to maritime performance, thereby guiding future empirical research and managerial interventions in crew development and organizational transformation.